Constitutional Submissions by General Courts in Georgia: Judicial Practice, Procedural Challenges, and Institutional Implications - Urushadze, Tamar (European Scientific Journal, ESJ, 2026)
The Constitution of Georgia establishes a centralized model of constitutional review entrusted to the Constitutional Court. Within this framework, courts of general jurisdiction participate in constitutional adjudication through the mechanism of constitutional submission, which allows them to suspend proceedings and refer questions of constitutionality to the Constitutional Court. Despite its structural importance, this mechanism has received limited doctrinal and theoretical analysis in Georgian legal scholarship. This article examines the procedural requirements, admissibility standards, and institutional implications of constitutional submissions filed by general courts. Employing doctrinal interpretation, comparative constitutional analysis with reference to the German referral model under Article 100(1) of the Basic Law, and case-law analysis of the Constitutional Court of Georgia, the study moves beyond descriptive review and critically evaluates the structural function of constitutional submission within a centralized constitutional system. The findings demonstrate that the Georgian framework contains interpretative ambiguities concerning the obligation to refer, inconsistencies in admissibility standards, and weaknesses in the legal consequences and enforcement of Constitutional Court decisions. More importantly, the article argues that constitutional submission should be conceptualized not merely as a procedural safeguard but as a structural instrument of judicial dialogue that directly affects constitutional supremacy and the effective protection of fundamental rights. By reframing constitutional submission as a mechanism of institutional interaction rather than a purely technical procedural device, the article contributes to constitutional law scholarship and proposes targeted legislative reforms aimed at clarifying referral obligations, strengthening enforcement guarantees, and enhancing the coherence of constitutional review in Georgia.